Sex-related differences in the morphology of the corpus callosum among adult Bangladeshi population: A CT-scan based study (Bangladesh Journal of Anatomy, 2020)
Context: The activities of the left and right cerebral hemispheres correlate via the corpus callosum. Its morphology has importance to diagnose and treatment for many neuropsychiatric diseases. The purpose of this study was to measure the different parameters of the corpus callosum in healthy adult Bangladeshi population to standardize the morphology of the human corpus callosum as well as to estimate the potential morphological sex difference which can provide a useful assessment of disease progression with implications on treatment planning. Methods: A cross sectional, analytical study was conducted on 35 adult male and 35 adult female Bangladeshi people aged ranging from 20-65 years in the Department of Anatomy, Dhaka Medical College, Dhaka from January 2017 to December 2017. CT scans of the brain in midsagittal view of both cerebral hemispheres were taken for this study. Then the maximum width of the genu and width of the body at the midpoint of the corpus callosum were measured from CT scan images by using a image measuring software program named RadiAnt DICOM Viewer, Version 4.0.3(64 bit). Data were analyzed by Unpaired student’s ‘t’ test. Results: The results revealed that the mean maximum width of genu of corpus callosum was 11.05±0.97 mm and 10.48±1.16 mm in male and female respectively. The mean maximum width of genu of corpus callosum (p